Level of agreement between cardiac output measurements using Nexfin® and thermodilution in morbidly obese patients undergoing laparoscopic surgery. (26th September 2016) - Schraverus, P.; Kuijpers, M. M.; Coumou, J.; Boly, C. A.; Boer, C.; van Kralingen, S.
Summary: Morbidly obese patients are at increased risk of intra‐operative haemodynamic instability, which may necessitate intensive monitoring. Non‐invasive monitoring is increasingly used to measure cardiac output; however, it is unknown whether the weight‐based algorithm utilised in these devices is applicable to patients with morbid obesity. We compared the level of agreement and trending ability of non‐invasive cardiac output measurements (Nexfin ® ) with the gold‐standard thermodilution technique in 30 morbidly obese patients undergoing laparoscopic surgery. Bland–Altman analysis revealed a mean (SD) bias of 0.60 (1.62) l.min −1 (limits of agreement −2.67 to 3.86 l.min −1 ) and the precision error was 46%. Polar plot analysis resulted in an angular bias of 2.61°, radial limits of agreement of −60.08° to 49.82° and angular concordance rate was 77%. Both agreement and trending were outside the Critchley criteria for the comparison of cardiac output devices with a gold‐standard. Nexfin has an unacceptable level of agreement compared with thermodilution for cardiac output measurement in morbidly obese patients.